Courses that Impact the Terminal Efficiency in the Dentistry Career at the University of Costa Rica (2007-2014) - Gómez-Fernández, Adrián (2024)
The main objective of this study was to determine the failure rates of the courses in the curriculum of the Dentistry degree program at the University of Costa Rica for the cohorts from 2007 to 2014. Data from 736 records were used. The variables considered were the following: gender, age at admission, nationality, marital status, children, domicile, previous high school attended, admission exam scores, and approved courses. The data were obtained from the Student Application System, physical records, and the Supreme Electoral Tribunal of Costa Rica. Descriptive, bivariate, and multivariate analyses were performed. Among the students, 98% were Costa Rican, 68% were female, 79% were admitted based on their admission exam scores, 43% were admitted at the age of 18 or younger, 50% came from public schools, 77% resided in the Greater Metropolitan Area, and 95% were single and childless. The majority of study dropouts occurred in the first four cycles of the dentistry degree. The courses with the lowest overall success rate in the curriculum were service courses: General Chemistry, Organic Chemistry, and Elemental Mathematics. Among the core courses, the Pediatric Dentistry and Orthodontics Clinic and the Endodontics Clinic had the highest failure rates. Moreover, there was a statistically significant difference between the approval rates of the physics course and the school of origin. In the Dentistry degree program at University of Costa Rica, the failure rate is high in the first four cycles of the program, which is when service courses are mainly offered. As for the core courses, the Pediatric Dentistry and Orthodontics Clinic and the Endodontics Clinic had the lowest success rates.